TINJAUAN YURIDIS PEMUTIHAN PAJAK KENDARAAN BERMOTOR UNTUK MENINGKATKAN PENDAPATAN ASLI DAERAH DI KOTA SEMARANG TAHUN 2023: Juridical Review of Motor Vehicle Tax Reduction in Increasing Original Regional Income in Semarang City in 2023 - Sukma, Sinta Ade; Primananda, Eko (Faculty of Law, Universitas Trisakti, 2025)
The central government delegates authority to regional governments to carry out household finances independently through decentralization with the aim of improving the welfare of the community. One of the regional government financing comes from regional taxes. This research adopts a normative juridical method with a descriptive approach, and analyzes secondary data supported by interviews. The PKB whitening program was implemented to encourage taxpayers to pay off their tax arrears by clearing late fines, as was done by Central Java Province, especially Semarang City. Based on Central Java Governor Regulation No. 9 of 2023, this program is designed to help vehicle owners fulfill their obligations without any fines/witnesses. Implementation includes determining objects and subjects, collection procedures, fee provisions, sanctions, and performance budgets. This shows an increase in motor vehicle tax revenue of 20.59% compared to the previous year. This program has proven effective in increasing regional income and taxpayer compliance.